Venous thromboembolism with contraceptive use in females with sickle cell traitAJOG Global Reports at a Glance - Angela K. Phillips, PhD, APRN; Candy Wilson, PhD, APRN, FAAN; Anwar E. Ahmed, PhD; Arun Shet, MD, PhD; Margaret Bevans, PhD, RN, FAAN (AJOG Global Reports)
BACKGROUND: Sickle cell trait is the carrier state for sickle cell disease and occurs in 1 in 13 births in Black and African American families. Individuals with sickle cell trait are permitted to serve in the military. Some research studies have shown that individuals with sickle cell trait may be at increased risk for thromboembolic events. Contraceptive use, specifically combined hormonal contraceptives containing both estrogen and progesterone, has been linked to an increased risk of thromboembolic events. No research has been done to determine if there is an increased risk of venous thromboembolism in a population of females with sickle cell trait who do or do not take combined hormonal contraceptives. OBJECTIVE: To determine if women with sickle cell trait who use combined hormonal contraceptives are at higher risk for venous thromboembolism compared with females with sickle cell trait who do not use combined hormonal contraceptives. Given the increased risk of venous thromboembolism in sickle cell trait individuals in the general population, we hypothesized that females with sickle cell trait exposed to combined hormonal contraceptives would experience higher venous thromboembolism rates than unexposed females with sickle cell trait. STUDY DESIGN: Population-based retrospective cohort study of females with sickle cell trait identified from the Military Data Repository to evaluate venous thromboembolism after exposure to combined hormonal contraceptives or without exposure to combined hormonal contraceptives. RESULTS: There were 15,440 unique females aged 18–44 years between 2005 and 2021 who had a diagnosis of sickle cell trait. Approximately 40% of females had an International Classification of Diseases code consistent with a prescription of a combined hormonal contraceptive. Thirty-three (0.2%) of the 15,440 females with sickle cell trait had experienced venous thromboembolism of any type. There was no difference in the prevalence of venous thromboembolism by combined hormonal contraceptive use (yes [0.18%] vs no [0.24%]; P=.454). Being older, married, nonactive-duty military status, smoking, and having a diagnosis of hypertension were associated with a higher prevalence of venous thromboembolism. CONCLUSION: Although there was a small number of venous thromboembolism events, the findings of this study suggest that the use of combined hormonal contraceptives in females with sickle cell trait is not associated with a detectable signal for increased venous thromboembolism risk as an outcome. Given the potential clinical benefit of combined hormonal contraceptives in pregnancy prevention and menstrual regulation in females, the concerns about combined hormonal contraceptive-associated venous thromboembolism in this population with sickle cell trait seem to be minimal.